Smart Power Dalam Pemasaran Relasional - Erik Bisri Alamsyah (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
This study is directed at building a basic and empirical theoretical model: Efforts to achieve strategic marketing outcomes based on the theory of relational marketing and power / power. Confirming and testing: the impact of smart power on trust, relational commitment, marketing cooperation, long-term relationship values (loyalty, relationship closeness, and chain messages); and the impact of long-term relationship values with strategic marketing outcomes (synergy of cooperation, competitive advantage and marketing performance). This study was conducted on tourism business organizations in Indonesia . The number of respondents was 315 leaders / managers of the organization. Measurement of research variables is done by using multiple indicators ,. in this research can be completed by positioning power / power and trust as a relational basis which is an antecedent of relational commitment and intensity of cooperation.Furthermore, long-term relationship values are social capital to obtain strategic marketing outcomes . Cooperation synergy is positioned as a mediating variable between behavioral results in relational marketing and strategic marketing results. So, the originality of the findings in this study is that the fabric of marketing relations between organizations will achieve higher marketing performance when based on relational marketing theory and power / power. The recommendations of this study, are: to build marketing cooperation must be based on an integrated market and resource base. At the operational and public policy level, the tourism industry in Indonesia needs to be developed by formulating a tourism development strategy based on local resources and culture.Keywords: Smart power ; Trust ; Relational Commitment